Inequivalent hadamard matrices from base sequences - Kotsireas I.S.; Koukouvinos C.; Simos D.E. (Utilitas Mathematica, 2009)
In this paper we construct inequivalent Hadamard matrices based on Yang multiplication methods for base sequences.